2021
DOI: 10.1038/s41419-021-03472-7
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circ_103820 suppresses lung cancer tumorigenesis by sponging miR-200b-3p to release LATS2 and SOCS6

Abstract: A growing number of circular RNAs (circRNAs) have been identified and verified in several cancers. However, highly efficient therapeutic methods based on circRNAs in lung cancer remain largely unexplored. In the present study, we identified a novel circular RNA, hsa_circ_103820, based on Gene Expression Omnibus (GEO) data. Functionally, overexpression of hsa_circ_103820 showed significant inhibitory effects on the proliferation, migration and invasion of lung cancer cells, and knockdown of hsa_circ_103820 play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…For instance, in most cases, it exhibits tumor-suppressive effects and is therefore downregulated, with examples of such tumors being colorectal cancer (CRC) (4-7), hepatocellular carcinoma (HCC) (8)(9)(10)(11)(12), pancreatic cancer (13,14), gastrointestinal stromal tumors (15), breast cancer (16)(17)(18), melanoma (19), glioblastoma (20), glioma (21), thyroid carcinoma (22), cemento-ossifying fibroma (23), esophageal cancer (24,25), oral squamous cell carcinoma (26), prostate cancer (27,28), renal cell carcinoma (29), bladder cancer (30), and malignant mesothelioma (31). However, as already noted, this microRNA can also be oncogenic in various types of cancers, with examples of such tumors being prostate cancer (32,33), lung cancer (34)(35)(36)(37)(38), oral squamous cell carcinoma (39), esophageal squamous cell carcinoma (40), breast cancer (41), colorectal cancer (42,43), neck cancer (44), cholangiocarcinoma (45), and hepatocellular carcinoma (46). Table I and Fig.…”
Section: Mir-200b-3p Function Is Dependent On Cancer Typementioning
confidence: 95%
See 2 more Smart Citations
“…For instance, in most cases, it exhibits tumor-suppressive effects and is therefore downregulated, with examples of such tumors being colorectal cancer (CRC) (4-7), hepatocellular carcinoma (HCC) (8)(9)(10)(11)(12), pancreatic cancer (13,14), gastrointestinal stromal tumors (15), breast cancer (16)(17)(18), melanoma (19), glioblastoma (20), glioma (21), thyroid carcinoma (22), cemento-ossifying fibroma (23), esophageal cancer (24,25), oral squamous cell carcinoma (26), prostate cancer (27,28), renal cell carcinoma (29), bladder cancer (30), and malignant mesothelioma (31). However, as already noted, this microRNA can also be oncogenic in various types of cancers, with examples of such tumors being prostate cancer (32,33), lung cancer (34)(35)(36)(37)(38), oral squamous cell carcinoma (39), esophageal squamous cell carcinoma (40), breast cancer (41), colorectal cancer (42,43), neck cancer (44), cholangiocarcinoma (45), and hepatocellular carcinoma (46). Table I and Fig.…”
Section: Mir-200b-3p Function Is Dependent On Cancer Typementioning
confidence: 95%
“…miR-200b-3p and its functions in lung cancer. In the case of lung cancer, miR-200b-3p mainly acts as an oncogene by regulating the expression of the ATP-binding cassette transporter A member 1 (ABCA1) (34), the transcriptional intermediary factor 1 γ (TIF1γ) (35), the large tumor suppressor kinase 2 (LATS2) as well as the suppressor of cytokine signaling 6 (SOCS6) (36), all of which are involved in tumor progression. Among these, the tumor-suppressor gene ABCA1 encodes a transmembrane protein that transports cholesterol to the outside of the cell and a study by Liu et al demonstrated that, by acting on this gene, miR-200b-3p could encourage non-small-cell lung cancer to grow and metastasize (34).…”
Section: Mir-200b-3p and Its Functions In Hepatocellular Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…Cell experiments revealed that high circ_0000079 expression inhibited cisplatin resistance in A549/DDP and H460/DDP cells, implying that circ_0000079 could be used as a prognostic indicator and therapeutic target for NSCLC. Chi et al ( 92 ) showed that overexpression of hsa_circ_103820 significantly inhibited the proliferation, migration and invasion of lung cancer cells, while knockdown of hsa_circ_103820 played a tumorigenic role. These results suggested that hsa_circ_103820 has a potential novel function as a tumor suppressor in lung cancer.…”
Section: Circrnas and The Prognosis Of Patients With Lung Cancermentioning
confidence: 99%
“…28 According to studies, the LATS2 gene is located at chromosome 13q12.11 and has the tumor suppressor gene functions; its expression is downregulated in lung cancer, prostate cancer, and GC, and has an inhibitory influence on tumor development. [29][30][31] LATS2 expression was discovered to be decreased in GC cells, and LATS2 overexpression in cells prevented cell invasion and migration and altered the expression of associated genes and proteins. These findings suggest that the LATS2 gene, as a tumor suppressor gene, has a strong inhibitory effect on GC cell invasion; however, the specific mechanism of action still needs to be explored in depth.…”
Section: Overexpression Of Linc01088 Decreased Cellmentioning
confidence: 99%